Effect of MHD on unsteady boundary layer flow past a sphere - Nurul Farahain Mohammad; Abdul Rahman Mohd Kasim; Anati Ali; Sharidan Shafie (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Magnetohydrodynamics (MHD) is a field of study which dealing with understanding the dynamic of fluid under the influence of magnetic presence. The effect of MHD in a fluid flow has the potential in controlling the separation of flow, optimizing the heat transfer involved or manipulate the velocity of fluidflow. In this paper, the separation times and flow characteristics of a viscous fluid flow past a sphere are investigated in the presence of magnetic field. In order to solve this problem, the dimensional equations that govern the fluid flow and heat transfer are transformed into dimensionless equations by usingappropriate dimensionless variables. The stream functions are introduced to connect and thus having a function that can represent both velocity u and v. Similarity variables are used to deduce the dimensionless governing equations into a system of nonlinear partial differential equations. This system of equations is solved numerically by using numerical scheme known as the Keller-Box method. The results attained are presented graphically and in tabular form